Protection of Privacy and Intellectual Property Rights in Digital Data Management in Indonesia - Imam Hanafi; Arief Fahmi Lubis (Eastasouth Institute, 2023)
This study looks into how intellectual property rights and privacy protection overlap when it comes to digital data management in Indonesia. With an emphasis on the legal, technological, and ethical aspects, the study uses a mixed-methods approach that includes case studies, legal analysis, and qualitative interviews. The analysis highlights the necessity for continual adaptation while revealing a strong legal framework, which is mainly supported by the Personal Data Protection Act (PDPA). The importance of cutting-edge technologies like blockchain and encryption is also highlighted by the findings, which also emphasize the moral issues that must be taken into account for responsible data management. The study finishes with practical suggestions that attempt to find a fine balance between protecting privacy and promoting innovation for decision-makers, corporations, and other interested parties.